Nitrogen and Phosphorus Recovery From Anaerobically Pretreated Agro-Food Wastes: A Review - Campos, José Luis; Crutchik, Dafne; Franchi, Óscar; Pavissich, Juan Pablo; Belmonte, Marisol; Pedrouso, Alba; Mosquera-Corral, Anuska; Val del Río, Ángeles (Frontiers in Sustainable Food Systems, 2019)
Anaerobic digestion (AD) is commonly used for the stabilization of agro-food wastes and recovery of energy as methane. Since AD removes organic C but not nutrients (N and P), additional processes to remove them are usually applied to meet the stringent effluent criteria. However, in the past years, there was a shift from the removal to the recovery of nutrients as a result of increasing concerns regarding limited natural resources and the importance given to the sustainable treatment technologies. Recovering N and P from anaerobically pretreated agro-food wastes as easily transportable and marketable products has gained increasing importance to meet both regulatory requirements and increase revenue. For this reason, this review paper gives a critical comparison of the available and emerging technologies for N and P recovery from AD residues.